The Impact Of Credit Shocks On Iraqi Banking Performance: An Analytical Study - et. al., Hussein Mohammed Sameer, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The current study aims to determine the nature of the impact of credit shock on banking performance by applying to The Sumer Commercial Bank of Iraq from 2004 to 2016. The banking sector is an important economic sector, which is the artery of the economy, which is the vibrant economic role in financial intermediation, mobilization of savings, and the granting of credit to various sectors, organizations. This study addresses the fundamental problem of Sumer Bank with sample search mechanisms. There is a knowledge gap around interpreting the relationship between the current research variables, represented by the independent variable credit shock and the variable dependent banking performance. New methods enable them to compete strongly within this sector and achieve high performance. The research found a set of scientific findings, including an honest impact relationship between credit shock and banking performance. The study results can protect the bank from falling into crises and financial problems and lead to improved services provided to customers. Thus, improving the standards of traditional and modern performance make their long-term goals and objectives.